Monochorionic twins with type III selective intrauterine growth restriction: case series and review of the literature - Lacunza Paredes, Rommel Omar (2019)
We present four cases of monochorionic twin pregnancies with diagnosis of type III selective intrauterine growth restriction, highlighting the ultrasonographic characteristics (evaluation of the umbilical artery intermittent reverse diastole and the superficial arterio-arterial anastomosis), its evolution during pregnancy and its follow-up during the first month of life.